Energy, environment, and technological change - National Bureau of Economic Research, Cambridge; Popp, David; Newell, Richard; Jaffe, Adam B. (Cambridge, MA, 2009)
"Within the field of environmental economics, the role of technological change has received much attention. The long-term nature of many environmental problems, such as climate change, makes understanding the evolution of technology an important part of projecting future impacts. Moreover, in many cases environmental problems cannot be addressed, or can only be addressed at great cost, using existing technologies. Providing incentives to develop new environmentally-friendly technologies then becomes a focus of environmental policy. This chapter reviews the literature on technological change and the environment. Our goals are to introduce technological change economists to how the lessons of the economics of technological change have been applied in the field of environmental economics, and suggest ways in which scholars of technological change could contribute to the field of environmental economics."